A Literature Survey on Market-Based Measures for the Decarbonization of Shipping - Lagouvardou, Sotiria; Psaraftis, Harilaos N.; Zis, Thalis (My University, 2020)
This paper aims to conduct an updated literature survey on the Market-Based Measures (MBMs) currently being proposed by various member states and organizations at the International Maritime Organization (IMO) or by the scientific and grey literature as a cost-effective solution to reduce greenhouse gas (GHG) emissions from ships. Τhe paper collects, summarizes, and categorizes the different proposals to provide a clear understanding of the existing discussions on the field and also identifies the areas of prior investigation in order to prevent duplication and to avoid the future discussion at the IMO to start from scratch. Relevant European Union (EU) action on MBMs is also described. Furthermore, the study identifies inconsistencies, gaps in research, conflicting studies, or unanswered questions that form challenges for the implementation of any environmental policy at a global level for shipping. Finally, by providing foundational knowledge on the topic of MBMs for shipping and by exploring inadequately investigated areas, the study addresses concrete research questions that can be investigated and resolved by the scientific and shipping community.
Keywords: Market-Based Measures; greenhouse gas emissions; International Maritime Organization; shipping; Eu Green Deal